A Specific Structural Requirement for Ergosterol in Long-chain Fatty Acid Synthesis Mutants Important for Maintaining Raft Domains in Yeast - Eisenkolb, Marlis (The American Society for Cell Biology, 2002)
Fungal sphingolipids contain ceramide with a very-long-chain fatty acid (C26). To investigate the physiological significance of the C26-substitution on this lipid, we performed a screen for mutants that are synthetically lethal with ELO3. Elo3p is a component of the ER-associated fatty acid elongase and is required for the final elongation cycle to produce C26 from C22/C24 fatty acids. elo3Δ mutant cells thus contain C22/C24- instead of the natural C26-substituted ceramide. We now report that under these conditions, an otherwise nonessential, but also fungal-specific, structural modification of the major sterol of yeast, ergosterol, becomes essential, because mutations in ELO3 are synthetically lethal with mutations in ERG6. Erg6p catalyzes the methylation of carbon atom 24 in the aliphatic side chain of sterol. The lethality of an elo3Δ erg6Δ double mutant is rescued by supplementation with ergosterol but not with cholesterol, indicating a vital structural requirement for the ergosterol-specific methyl group. To characterize this structural requirement in more detail, we generated a strain that is temperature sensitive for the function of Erg6p in an elo3Δ mutant background. Examination of raft association of the GPI-anchored Gas1p and plasma membrane ATPase, Pma1p, in the conditional elo3Δ erg6(ts) double mutant, revealed a specific defect of the mutant to maintain raft association of preexisting Pma1p. Interestingly, in an elo3Δ mutant at 37°C, newly synthesized Pma1p failed to enter raft domains early in the biosynthetic pathway, and upon arrival at the plasma membrane was rerouted to the vacuole for degradation. These observations indicate that the C26 fatty acid substitution on lipids is important for establishing raft association of Pma1p and stabilizing the protein at the cell surface. Analysis of raft lipids in the conditional mutant strain revealed a selective enrichment of ergosterol in detergent-resistant membrane domains, indicating that specific structural determinants on both sterols and sphingolipids are required for their association into raft domains.